What was once east pakistan - Husain, Syed Shahid ([S.l.] : Oxford University Press, 2010)
This book relates the personal experiences of the author and looks at East Pakistan from his perspective. The author served in East Pakistan for two years during the crucial period of 1969 to 1971. The book also includes an account of a cyclone that hit East Pakistan in 1970. He has analyzed the roles of the three major players in the game viz. General Yahya Khan, Zulfikar Ali Bhutto and Mujibur Rehman and the role of the US, which has been involved in Pakistan right from the time of independence in 1947.
Keywords: Bangladesh; India-Pakistan Conflict--(1971); Revolution (Bangladesh : 1971)